Identification Of Psychosocial Problems In Tourism Awareness Groups (Pokdarwis) In Panji Tourism Village - Widiarta, Made Bayu Oka; Shofi Khaqul Ilmy; Wigutomo Gozali; Ida Ayu Made Sari Santi Tisnasari; Galih Gayatri (HealthCare Nursing Journal, 2025)
Background: A person's mental health will affect the economy, happiness and others. So mental health is important for every element without exception, tourism awareness groups (pokdarwis). The current era or post-pandemic requires pokdarwis to again promote tourism to support their economy and family. However, not a few pokdarwis feel worried or experience psychosocial problems, afraid that the pandemic will recur. This psychosocial condition will affect the interest, enthusiasm and motivation of pokdarwis members to innovate to rise and create attractive tourist villages that have good economic income potential after the pandemic. Objective: The researcher's goal is to identify psychosocial problems of pokdarwis in Panji Village as a tourist village destination. Method: This research was conducted descriptively quantitatively with a cross-sectional approach. The research population was the tourism awareness group (pokdarwis) of Panji Village, with samples taken in clusters in Banjar that has pokdarwis. The minimum number of samples taken was 70 respondents. The instrument used was the SQR-20 questionnaire to assess psychosocial factors (energy, cognitive, physiological, depression and anxiety) in Panji Village. Data collection used structured interviews after the study was declared ethically feasible. The data collected will be analyzed univariately. Results: The results of the study showed that most members of the tourism awareness group (Pokdarwis) in Panji Village currently have low income, namely 38 people (54.3%) and most showed symptoms of psychosocial mental health problems, namely emotional mental disorders (energy, cognitive, depression, physiological, anxiety) as many as 42 people (60%). Conclusions: Post-pandemic psychosocial problems show that most respondents show symptoms of psychosocial mental health problems, namely emotional mental disorders (energy, cognitive, depression, physiological, anxiety) as many as 42 people (60%).